Lab-in-syringe automated protein precipitation and salting-out homogenous liquid-liquid extraction coupled online to UHPLC-MS/MS for the determination of beta-blockers in serum - Yıldırım, Sercan; Fikarová, Kateřina; Pilařová, Veronika; Nováková, Lucie; Solich, Petr; Horstkotte, Burkhard (Analytica chimica acta, 2023)
A sample preparation method involving tandem implementation of protein precipitation and salting-out homogenous liquid-liquid extraction was developed for the determination of beta-blockers in serum. The entire procedure was automated using a computer-controlled syringe pump following the Lab-In-Syringe approach. It is based on the denaturation of serum proteins with acetonitrile followed by salt-induced phase separation upon which the proteins accumulate as a compact layer at the interphase of the solutions. The extract is then separated and diluted in-syringe before being submitted to online coupled UHPLC-MS/MS. A 1 mL glass syringe containing a small stir bar for solution mixing at up to 3000 rpm, was used to deal with sample volumes as small as 100 μL. A sample throughput of 7 h-1 was achieved by performing the chromatographic run and sample preparation procedure in parallel. Linear working ranges were obtained for all analytes between 5 and 100 ng mL-1, with LOD values ranging from 0.4 to 1.5 ng mL-1. Accuracy values in the range of 88.2-106% and high precision of <11% RSD suggest applicability for routine analysis that can be further improved using deuterated standards.
Keywords: tandemová hmotnostní spektrometrie; extrakce kapalina-kapalina; Tandem Mass Spectrometry; Chromatography, High Pressure Liquid; Liquid-Liquid Extraction; Sodium Chloride; vysokoúčinná kapalinová chromatografie; injekční stříkačky; chlorid sodný; Syringes